2018
DOI: 10.1016/j.gene.2018.05.034
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of physis tissue by RNA sequencing

Abstract: The physis is a well-established and anatomically distinct cartilaginous structure that is crucial for normal long-bone development and growth. Abnormalities in physis function are linked to growth plate disorders and other pediatric musculoskeletal diseases. Understanding the molecular pathways operative in the physis may permit development of regenerative therapies to complement surgically-based procedures that are the current standard of care for growth plate disorders. Here, we performed next generation RN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…This protocol mimics the process of chondrocyte differentiation in the growth plate, with cells characteristic of hypertrophic chondrocytes in their morphology as well as their gene expression being obtained after 56 days in 3D culture. Genes that are highly upregulated in the physis but not articular cartilage, such as MATN3 and COL9A2 (Paradise et al, 2018), were expressed in the course of induction, supporting the validity of our model to research disorders of the growth plate.…”
Section: Discussionsupporting
confidence: 61%
“…This protocol mimics the process of chondrocyte differentiation in the growth plate, with cells characteristic of hypertrophic chondrocytes in their morphology as well as their gene expression being obtained after 56 days in 3D culture. Genes that are highly upregulated in the physis but not articular cartilage, such as MATN3 and COL9A2 (Paradise et al, 2018), were expressed in the course of induction, supporting the validity of our model to research disorders of the growth plate.…”
Section: Discussionsupporting
confidence: 61%
“…Differential gene expression analysis was conducted using RPKM values as previously described. 53 Genes with an average RPKM <0.1 in both treatment groups were excluded from the analysis. GO term overlap was conducted using the Compute Overlap tool in the Molecular Signature Database (MSigDB) v6.2 suite on the Gene Set Enrichment Analysis (GSEA) website.…”
Section: Rna Seqmentioning
confidence: 99%
“…Moreover, when comparing DE genes in GP from different ages, we observed that through aging, more shared DE genes were found between 21 and 35 days and between 35 and 42 days of age, than when 21 and 42 days were compared ( Figure 4 ). When looking at the 12 exclusively DE genes between normal and FHS-affected broilers at 21 days of age ( SHISA3, FNDC1, ANGPTL7, LEPR, OXTR, COL16A1, BOC, E NSGALG00000049529, RASD2, GDF10 ENSGALG00000045154, and THSD7B) , they were mainly related to WNT and FGF signaling ( Amanatullah et al, 2014 ), bone metabolism ( Nilsson et al, 2007 ; Di Benedetto et al, 2014 ; Lui et al, 2018 ), angiogenesis ( Shang et al, 2015 ; Huang et al, 2021 ), chondrogenesis ( Sekiya et al, 2002 ; Paradise et al, 2018 ) and Hedgehog signaling pathway ( Kavran et al, 2010 ; Xavier et al, 2016 ). In this way, it is possible to highlight that DE genes between normal and affected broilers at 21 days of age were mainly related to endochondral ossification, while when GP and AC at 35 and 42 days of age were evaluated ( Peixoto et al, 2019 ; Oliveira et al, 2020 ; Hul et al, 2021 ; Goldoni et al, 2022 ), there were several DE genes related to other biological processes, such as inflammation, defense response, chemotaxis, within others.…”
Section: Discussionmentioning
confidence: 99%